Principles of Genetics - Snustad, D. Peter Simmons, Michael J (John Wiley, 1997)
One of the fundamentals behind this text is that genetics is not a static body of knowledge. Historical and contemporary examples are therefore used throughout, and concepts are presented in an evolutionary context whenever possible.